Badinsk zeolite application for ground water treatment; IFOST 2012; Vol. 1 - Nazarenko O. B. Olga Bronislavovna (Section 1. Chemical engineering and "Green technology", 2012)
In this paper the natural zeolite from the Badinsk deposit (Byryat Republic) was tested as adsorbent forFe2+, Fe3+ removal from aqueous solutions and Kozhevnikovsky ground water (Tomsk Region) under dynamic conditions. The physicochemical and adsorption properties of the zeolite were studied by XRD, TGA, DTA, FTIR spectroscopy and chemical analyses. It is found that Fetotal removal efficiency achieved from 69 wt% to 100 wt% depending on the initial concentration.